2005
DOI: 10.1136/emj.2005.003079
|View full text |Cite
|
Sign up to set email alerts
|

Simple measures to reduce the rate of contamination of blood cultures in Accident and Emergency

Abstract: Objectives: To reduce the contamination rate of blood cultures taken in the Accident and Emergency (A&E) department. Methods: The standard blood culture sampling kit was supplemented with an instruction sheet on the optimal method for drawing blood cultures and a large 62% ethyl alcohol impregnated wipe.Results: There was a statistically significant reduction in the number of contaminants (p = 0.03). Conclusions: Simple measures to encourage skin disinfection and appropriate sampling technique will reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 8 publications
2
30
2
1
Order By: Relevance
“…10 Antiseptics with more rapid drying time are preferred over povidone-iodine to allow samples to be obtained more quickly. 10 In 1 study, 14 use of blood culture sampling kits significantly reduced contamination rates from 24% to 8%. The kit included sample bottles, an instruction sheet, and a large wipe impregnated with 62% ethyl alcohol for cleansing the skin before venipuncture.…”
Section: Recommendations For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…10 Antiseptics with more rapid drying time are preferred over povidone-iodine to allow samples to be obtained more quickly. 10 In 1 study, 14 use of blood culture sampling kits significantly reduced contamination rates from 24% to 8%. The kit included sample bottles, an instruction sheet, and a large wipe impregnated with 62% ethyl alcohol for cleansing the skin before venipuncture.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…The kit included sample bottles, an instruction sheet, and a large wipe impregnated with 62% ethyl alcohol for cleansing the skin before venipuncture. 14 …”
Section: Recommendations For Practicementioning
confidence: 99%
“…Several studies have shown that reducing BC contamination is possible through simple, inexpensive interventions -typically a combination of education, feedback and use of BC packs (Madeo et al, 2005;Murillo et al, 2011;Marini and Truog, 2012;Youssef et al, 2012;Self et al, 2013;Harding and Bollinger, 2013). These studies have principally focused on reducing rates of contaminated cultures in order to reduce the costs associated with false positive cultures.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinically irrelevant bacteria from the patient's skin, often termed BC contaminants, can also be cultured if a proper sampling technique is not observed. A contamination rate of <3% is considered acceptable, (Schifman et al, 1998; Department of Health, 2007) but contamination rates often exceed this, particularly in emergency departments (ED) (Madeo et al, 2005;Gander et al, 2009;Murillo et al, 2011;Self et al, 2013;Harding and Bollinger, 2013). Concern has been raised over the clinical and financial cost of BC contamination.…”
Section: Introductionmentioning
confidence: 99%
“…the inclusion of simple measures such as enclosing advisory leaflets, posters and providing reminder chit on blood culture bottles could be effective strategies. 8 throughout the study, the main challenge was keeping in tract of new housemen to be included in the program as fast turnaround time of housemen rotation in medical department as well as flexi-hours working hours were the greatest challenge. Somehow we achieved 95% coverage of housemen from medical department for the campaign.…”
Section: Discussionmentioning
confidence: 99%